Adaptasi Masyarakat Terhadap Bencana Banjir Lahar Studi Kasus : Kemiren, Srumbung, Magelang, Jawa Tengah - Iswardoyo, Jati (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
Merapi Volcanic eruptions produce a material that is potentially causing harm due to dangerous lava flood. However, on the other side, Mount Merapi is also areas that support continuity of livelihood systems for local communities in the slopes of Mount Merapi. The government has implemented sabo technology in the Village of Kemiren, Srumbung District, Magelang regency, Jawa Tengah. This study examines and analyzes the adaptation strategies, specifically adopted lava floods. Adaptation of community-based lava flood involving all available resources phenomenon, such as natural, human and institutional. The study used a qualitative approach through Focus Group Discussion and Depth Interview. Using secondary data and primary data, the scope of the study covers the mining, agricultural and environmental sectors. The results showed a positive role in Kemiren communities in lava floods adaptation, by involving all the potential resources. Kemiren community has a good understanding of the hazards risk. The application of Sabo technology can be done synergistically with Kemiren village community life.